2023
DOI: 10.1002/nop2.1625
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a mutual goal‐based continuous care program on self‐management behaviour and health outcomes in patients after percutaneous coronary intervention: A randomized controlled trial

Abstract: Aims To evaluate the effects of mutual goal‐based continuous care program on the outcomes of patients with coronary heart disease (CHD) after percutaneous coronary intervention (PCI). Design A single‐blinded randomized controlled trial. Methods 87 patients with CHD after PCI in Hangzhou, Zhejiang, China, were randomly divided into study ( n = 42) and control ( n = 45) groups. The control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
(54 reference statements)
0
0
0
Order By: Relevance
“…Tan et al [24] applied a behavior-changing nursing intervention to patients with CHD after PCI and found that applying the behavior change theory for cardiac rehabilitation management of patients with CHD after PCI can improve the lifestyle and QOL of patients. Zhu et al [25] implemented a mutual goal-based continuous care program for patients with CHD after PCI over a 12-week period. They concluded that this program enhanced the self-management behavior of patients with CHD after PCI, improved patient QOL and satisfaction, and controlled the unscheduled readmission rate.…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al [24] applied a behavior-changing nursing intervention to patients with CHD after PCI and found that applying the behavior change theory for cardiac rehabilitation management of patients with CHD after PCI can improve the lifestyle and QOL of patients. Zhu et al [25] implemented a mutual goal-based continuous care program for patients with CHD after PCI over a 12-week period. They concluded that this program enhanced the self-management behavior of patients with CHD after PCI, improved patient QOL and satisfaction, and controlled the unscheduled readmission rate.…”
Section: Discussionmentioning
confidence: 99%